2008
DOI: 10.1536/ihj.49.403
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-B-Type Natriuretic Peptide Level Is Depressed in Patients With Significant Coronary Artery Disease Who Have High Body Mass Index

Abstract: SUMMARYThe aim of this study was to determine how body mass index (BMI) influences the N-terminal pro-B-type natriuretic peptide (NT-proBNP) level in patients with significant coronary artery disease (CAD).A total of 348 patients (61.5 ± 9.2 years, male 67.5%) who had normal left ventricular systolic function were enrolled. All patients underwent percutaneous coronary intervention. We excluded patients with acute myocardial infarction, chronic heart failure, or renal dysfunction. Baseline NT-proBNP level was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…In this study, the average level (around 24.7 kg/m 2 ) and distribution of BMI was comparable with other Asian studies [4], [13], but it was much lower in comparison with the western populations (around 28 kg/m 2 ) [2], [3], [5], [7]. Of this study populations, 46% was normal weight (BMI<25 kg/m 2 ), 51% overweight (BMI = 25–29.9 kg/m 2 ), and 3% obese (BMI≥30 kg/m 2 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the average level (around 24.7 kg/m 2 ) and distribution of BMI was comparable with other Asian studies [4], [13], but it was much lower in comparison with the western populations (around 28 kg/m 2 ) [2], [3], [5], [7]. Of this study populations, 46% was normal weight (BMI<25 kg/m 2 ), 51% overweight (BMI = 25–29.9 kg/m 2 ), and 3% obese (BMI≥30 kg/m 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…Several recent reports suggest that obesity, as indexed by elevated body mass index (BMI), may also affect NT-proBNP levels, with lower circulating levels in those with higher BMI in subjects with acute or chronic heart failure [2], [3], significant coronary artery disease or acute myocardial infarction [4], [5] and healthy general populations [6]. However, isolated study showed that obesity is not statistically associated with NT-proBNP in asymptomatic patients with hypertension [7].…”
Section: Introductionmentioning
confidence: 99%
“…Log adjustment was used to account for the skewed distribution of NT-proBNP. Nevertheless, the consistency of our results with similar studies in heart failure7 16 or in patients undergoing percutaneous coronary intervention with a preserved LVEF10 also support the validity of our clinical findings.…”
Section: Discussionsupporting
confidence: 89%
“…Among these factors, BMI emerged as one of the most powerful determinants of circulating levels of the propeptide; a 3% decrease in NT-proBNP value was found per unit increase in BMI. A similar relationship has also been reported in chronic stable heart failure7 18 or in patients with a preserved LVEF undergoing percutaneous coronary intervention 10. The validity of our findings, on a large sample size of more than 2000 patients, is supported by its consistency across both sexes, by the adjustment methods with numerous covariates, including LVEF, and by the use of matching procedures.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, ANP infusion immediately after coronary angioplasty in patients with acute myocardial infarction has been able to prevent LV dilation and remodelling more efficiently than isosorbide dinitrate [86]. On the other hand, in patients with CAD, low levels of NT-proBNP are inversely correlated with BMI, with the NTproBNP levels not elevated in patients with CAD and high BMI [92]. Thus low NP levels may contribute to the pro-inflammatory state, as well as to the endothelial dysfunction and reduced coronary reserve in obese patients with the MS.…”
Section: Cardiovascular Damage In Dysmetabolic Patients: Possible Invmentioning
confidence: 99%